2006
DOI: 10.1111/j.1420-9101.2006.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombination is suppressed and variability reduced in a nascent Y chromosome

Abstract: Several hypotheses have been elaborated to account for the evolutionary decay commonly observed in full‐fledged Y chromosomes. Enhanced drift, background selection and selective sweeps, which are expected to result from reduced recombination, may all share responsibilities in the initial decay of proto‐Y chromosomes, but little empirical information has been gathered so far. Here we take advantage of three markers that amplify on both of the morphologically undifferentiated sex chromosomes of the European tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Berset‐Brandli et al . () found that molecular diversities on Y, X and autosomes in H. arborea fall roughly in the ratio 1:3:4. Such ratios are expected for neutrally evolving sex chromosomes that do not recombine.…”
Section: Discussionmentioning
confidence: 98%
“…Berset‐Brandli et al . () found that molecular diversities on Y, X and autosomes in H. arborea fall roughly in the ratio 1:3:4. Such ratios are expected for neutrally evolving sex chromosomes that do not recombine.…”
Section: Discussionmentioning
confidence: 98%
“…Recombination in H. arborea males is suppressed on all sex-linked markers and drastically repressed on autosomes [29], arguing against local mechanisms such as inversions [37]. Genome-wide effects with phenotypic-sex dependence are likely to stem from meiotic or epigenetic processes [38].…”
Section: Discussionmentioning
confidence: 99%
“…All Eurasian tree frogs have homomorphic sex chromosomes [27]. Male heterogamety was first evidenced in Hyla arborea by sex differences in the allelic distribution of microsatellite markers [28][29]. Mapping linkage groups through sibship analyses identified nine sex-linked markers, which all revealed complete absence of male recombination, despite overlapping X-Y allelic distributions [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the reasons to focus on H. arborea are twofold. First, documenting the effect of its lek‐breeding mating system on sex‐specific effective sizes should help understanding the dynamics of genetic variance at sex‐specific loci and the evolution of its nascent sex chromosomes (Berset‐Brändli et al 2006, 2007, 2008a; Niculita‐Hirzel et al 2008). Although the proto‐Y chromosome has been shown to display lower levels of standing genetic diversity than does the proto‐X (Berset‐Brändli et al 2007), the difference seems fully accounted for by the numbers of copies per breeding pair (3X vs. 1Y), which appears at odds with the drop in male effective population size expected from its lekking habits (Berset‐Brändli et al 2007).…”
Section: Opportunity For Sexual Selection On Male Mating Success (Ipmentioning
confidence: 99%